Did sexist voters bring Italy its first female Prime Minister? - Mauro Bertolotti; Laura Picciafoco; Patrizia Catellani (QOE-IJES)
We examined the role of hostile sexism in vote at the 2022 general election in Italy, where the largest among center-right parties was led by a woman, Giorgia Meloni. We analyzed data from a sample of 1635 voters who participated in the 2022 ITANES survey. Hostile sexism was associated with male gender, lower education, higher religiosity, and right-wing orientation. As to vote choice, hostile sexism was positively associated with vote for Brothers of Italy and the other center-right parties. However, such association was significantly moderated by the evaluation of Giorgia Meloni, and disappeared among voters with a positive evaluation of her. Discussion focusses on the interplay between gender-related attitudes and candidate-based heuristics in vote choice.